THE RESPONSE TO CHALLENGING BEHAVIOR AS A BARRIER TO SOCIAL INCLUSION ERASMUS+ PROJECT PARTICIPANTS’ PERSPECTIVES ON POLICY AND PRACTICE - GRUNG, ROLF MAGNUS; ODROWĄŻ-COATES, ANNA; TAH, JUDE; MALORET, PAUL; KISS, JULIEN; ORTAN, FLORICA (Society Register, 2021)
The paper is the result of collaboration between seven European universities and covers health, social pedagogy, and special education programs, aimed at the removal of barriers to social inclusion and social participation facing children and young adults with intellectual and developmental disabilities (IDD). The collaboration received funding from the Erasmus+ Intensive Program with the aim of developing a common curriculum on social inclusion for children and young adults with IDD. Identifying variables that support inclusion for individuals with IDD who engage in challenging behavior is critically important and this paper is built on reviewing social and educational policies from 5 European countries in order to do so. The paper reveals loopholes and paradoxes in policy that hinder social inclusion when addressing challenging behavior. The greatest challenges identified by the researchers are the gaps in training for different professions and the lack of overarching legislation for these professions. Another issue identified is government tolerance of a lack of clear competencies and codes of conduct amongst unregulated service providers.